Rituximab in der Behandlung der erworbenen Hämophilie A bei einem Patienten mit Polymyalgia rheumatica - Braunert, L.; Bruegel, M.; Pfrepper, C.; Thiery, J.; Niederwieser, D. (Hämostaseologie, 2010)
Acquired hemophilia A is a rare but potentially life-threatening bleeding disorder. It is caused by the development of autoantibodies directed against coagulation factor VIII in adults or elderly patients, who do not have a personal or family history of bleeding. Case: A man (age: 76 years) on prednisone and leflunomide for polymyalgia rheumatica developed spontaneous severe haematomas. The patient was diagnosed with acquired factor VIII deficiency (FVIII activity 1.2%, FVIII inhibitor 31.7 BU). Due to the active bleeding diathesis, treatment was administered with activated prothrombin complex concentrates (FEIBA®, Baxter). Immunosuppressive treatment with a combination of oral prednisone (1 mg/kg daily) and cyclophosphamide (1,5 mg/kg daily) was administered to reduce the FVIII inhibitor. However, after two weeks of treatment, FVIII was only 3% and no clinical improvement was observed. Treatment with the anti CD20 monoclonal antibody rituximab intravenously at 375 mg/m2 once weekly for four consecutive weeks was started. The patient showed rapid clinical improvement following rituximab treatment. He achieved a complete remission defined as return to normal FVIII activity and undetectable FVIII inhibitor titer. After a follow-up of six months no relapse occurred. Conclusion: Rituximab appears an effective and well-tolerated treatment for patients with acquired haemophilia.
Keywords: Acquired haemophilia; rituximab; polymyalgia rheumatica